Unicrypt: A Constructive Approach Towards Rainbow Table Vulnerability - Dagar, Mohit; Saini, Nandit; Sankla, Ashish; Naresh, Himanshu (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2015)
This project shows how we can eliminate the threat of password cracking by rainbow table. In this project we had made an encipher which encrypts our message or password in such a way that it becomes impossible to make a complete rainbow table for it which thus protects us from rainbow table attack used by professional hackers to crack the password. The encipher encrypts our message such that a different hash value is created every time, even if you encrypt the same message more than one time.